Basement Configuration and Delineation of Banyumas Sub-Basin Based On Gravity Data Analysis - Imam Setiadi (Pusat Survei Geologi, 2017)
Many oil and gas seepages occurred on thesurface of Banyumas Basin as one of the active petroleum systems manifestation. Geological complexity of this basin makes it difficult to discover the oil and gas reserves unlike the basin of the East and West Java area. The aims of this research are to determine the subsurface geological structure patterns, distribution of sedimentary sub-basin, and Â basement configuration. Gravity data of Banyumas and surrounded area is analysed by using spectral analysis, moving average filter, and 2D forward modelling. The gravity data delineation analysis resulting about six sedimentary sub basins with depocentre of 5.5 km positioned at Purbalingga and Karangkobar Sub-basin. The structural pattern derived from residual gravity anomaly shows a relative southeast-northwest strike-slip fault and an east-west trend basement high pattern. Concerning from the oil and gas seepage presence in the study area, sufficient sedimentary rock thickness, and supporting petroleum system, this region is considered as an attractive subbasin for further petroleum prospect investigation.Â Keywords : gravity analysis, sedimentary basin, spectral analysis, moving average, 2D modelling